Thermal conductivity measurements and modeling of thin films - Chung, George Kit Chen. (2008)
In order to study thermal conductivities of ta-C and SiC>2 thin films, the PPR system was developed. The analytical expression applied for data extraction was obtained from the transmission-line theory of heat conduction. The latter was originated from Hui and Tan [S.l] and is now extended to include thermal resistance, pulse shape factor and various boundary conditions. Various pulse shapes are also studied to understand on their effect in curve fitting a three-layer sample, Au/ta-C/Si. It is found that the fitted thermal conductivity of Au is highly pulse shape dependent, but the pulse shape does not affect the thermal property determination of ta-C.